Systolic dysfunction and complete heart block as complications of fulminant myocarditis in a recovered COVID-19 patient. Issue 4 (October 2021) - Nikoo, Mohammad Hossein; Mozaffari, Reza; Hatamnejad, Mohammad Reza; Bazrafshan, Mehdi; Kasaei, Mohammad; Bazrafshan, Hamed
Abstract: We describe the first case report of fulminant myocarditis and complete heart block which was initially presented by severe systolic dysfunction and tachyarrhythmia, in a patient who recently recovered from covid-19. Continuous close follow-up should be considered for patients infected with COVID-19 after discharge, especially for those with any metabolic and pharmacologic risk factors for the conductive block to recognize these rare complications and reverse CHB early by administering a high dose of corticosteroid or other anti-inflammatory medications. <Learning objective: To illustrate the presentation of COVID-19 fulminant myocarditis by severe systolic dysfunction, tachyarrhythmia, and different degrees of atrioventricular block. To introduce the proper management of fulminant myocarditis in a patient who recently recovered from covid-19.>